(untitled) (Web of Teachers: Inderscience Research, 2025)
Adolescent heroes in literature serve as compelling figures who reflect personal growth, moral dilemmas, and societal influences. This study explores the character development of adolescent protagonists and their artistic representation in literature. The research investigates how authors shape these characters’ psychological and emotional evolution, considering cultural and historical contexts. Through qualitative analysis, we examine key literary works that showcase adolescent heroism and its artistic interpretation. The findings highlight common narrative techniques and thematic elements that contribute to their realistic portrayal, offering insights into their broader literary and educational significance.